Immunoglobulin A anti-phospholipid antibodies in Swedish cases of systemic lupus erythematosus: associations with disease phenotypes, vascular events and damage accrual. (12th September 2018) - Frodlund, M; Vikerfors, A; Grosso, G; Skogh, T; Wetterö, J; Elvin, K; Gunnarsson, I; Kastbom, A; Dahlström, Ö; Rönnelid, J; Svenungsson, E; Sjöwall, C
Summary: Immunoglobulin (Ig) G- and IgM-class anti-cardiolipin antibodies (aCL) and lupus anti-coagulant (LA) are included in the 1997 update of the American College of Rheumatology (ACR-97) systemic lupus erythematosus (SLE) criteria. Despite limited evidence, IgA-aCL and IgA anti-β2 -glycoprotein-I (anti-β2 GPI) were included in the 2012 Systemic Lupus International Collaborating Clinics criteria. The present study aimed to evaluate IgG-/IgA-/IgM-aCL and anti-β2 GPI occurrence in relation to disease phenotype, smoking habits, pharmacotherapy, anti-phospholipid syndrome (APS) and organ damage among 526 Swedish SLE patients meeting ACR-97. Patients with rheumatoid arthritis (n = 100), primary Sjögren's syndrome (n = 50) and blood donors (n = 507) served as controls. Anti-phospholipid antibodies (aPL) were analysed by fluoroenzyme-immunoassays detecting aCL/anti-β2 GPI. Seventy-six (14%) SLE cases fulfilled the Sydney APS-criteria, and ≥ 1 aCL/anti-β2 GPI isotype (IgG/IgA/IgM) occurred in 138 SLE patients (26%). Forty-five (9%) of the SLE cases had IgA-aCL, 20 of whom (4%) lacked IgG-/IgM-aCL. Seventy-four (14%) tested positive for IgA anti-β2 GPI, 34 (6%) being seronegative regarding IgG/IgM anti-β2 GPI. Six (1%) had APS manifestations but were seropositive regarding IgA-aCL and/or IgA anti-β2 GPI in the absence of IgG/IgM-aPL and LA. Positive LA and IgG-aPL tests were associated with most APS-related events and organ damage. Exclusive IgA anti-β2 GPI occurrence associated inversely with Caucasian ethnicity [odds ratio (OR) = 0·21, 95% confidence interval (CI) = 0·06–0·72) and photosensitivity (OR = 0·19, 95% CI = 0·05–0·72). Nephritis, smoking, LA-positivity and statin/corticosteroid-medication associated strongly with organ damage, whereas hydroxychloroquine-medication was protective. In conclusion, IgA-aPL is not rare in SLE (16%) and IgA-aPL analysis may have additional value among SLE cases with suspected APS testing negative for other isotypes of aPL and LA. Graphical Abstract: